Analysis of counter flow injection technique at elevated enthalpy hypersonic reacting flows. (January 2022) - Patil, Ajay; Kumar, Shailendra; Kulkarni, Vinayak
Highlights: Various flow features computed with perfect and real gas solvers for counterflow jet are compared. Percentage drag reduction increases for real gas flow at higher stagnation enthlapy than perfect gas flow. Lower wall heat flux is noticed for real gas flow at higher stagnation enthlapy than perfect gas flow. Effectiveness of the jet is higher for wave drag and wall heat flux reduction at higher stagnation enthalpy. Abstract: Large wave drag and high surface heating are common problems encountered at hypersonic speeds and these should be properly dealt for the effective and safe flights. Many studies have been carried out to mitigate these problems by employing various active and passive techniques but most of these computational or experimental studies account lower stagnation enthalpy flows or perfect gas assumption. Hence the current study examines the effect of higher freestream stagnation enthalpy on flow field alteration for counter - jet drag reduction technique for a hemispherical object. Results also includes the real gas effects on flow field, wave drag and wall heat flux. Further the effect of various flow parameters is observed on surface pressure distribution, surface heat flux and drag force for the hypersonic flow over the hemisphere, using the in house developed perfect gas and non - equilibrium N - S flow solvers. Results reveal that the perfect gas assumption overestimates surface properties and wave drag value. Drag coefficient reduces with freestream total enthalpy ( H o ) in the presence of real gas effects. Around 30% drag reduction is observed at H o =1 MJ/kg for Mach number 5 as compared to no - jet case and this reduction increases at higher freestream total enthalpy for same injection pressure ratio. Higher pressure ratio of the jet results in lower surface pressure and Stanton number on the object which gives lower wave drag.